2015
DOI: 10.1021/jacs.5b07093
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Probing of the Active Site Geometry of Ultrathin Nanowires for the Oxygen Reduction Reaction

Abstract: To create truly effective electrocatalysts for the cathodic reaction governing proton exchange membrane fuel cells (PEMFC), namely the oxygen reduction reaction (ORR), necessitates an accurate and detailed structural understanding of these electrocatalysts, especially at the nanoscale, and to precisely correlate that structure with demonstrable performance enhancement. To address this key issue, we have combined and interwoven theoretical calculations with experimental, spectroscopic observations in order to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 80 publications
(142 reference statements)
3
41
1
Order By: Relevance
“…Figure 1b displays the corresponding Ramanspectra of the two samples, which are used to investigate the structure of rGO and the interaction between PtCu particles and rGO. [13] From the magnified TEM image of as ingle nanowires hown in Figure 2d,w ell-resolved lattice fringesc an be clearly observed with the lattice spacings of 0.230 nm, corresponding to the {111}p lane of face-centered cubic (fcc) PtCu. Generally,t he I D /I G ratio is related to the size of sp 2 domains.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Figure 1b displays the corresponding Ramanspectra of the two samples, which are used to investigate the structure of rGO and the interaction between PtCu particles and rGO. [13] From the magnified TEM image of as ingle nanowires hown in Figure 2d,w ell-resolved lattice fringesc an be clearly observed with the lattice spacings of 0.230 nm, corresponding to the {111}p lane of face-centered cubic (fcc) PtCu. Generally,t he I D /I G ratio is related to the size of sp 2 domains.…”
Section: Resultsmentioning
confidence: 96%
“…Such 1D anisotropic PtCu nanowires with ultrathin sizea nd high aspect ratio would be conducive to the electrocatalysis owing to the path directing effect of the structural anisotropy and enormouss urface atoms. [13] From the magnified TEM image of as ingle nanowires hown in Figure 2d,w ell-resolved lattice fringesc an be clearly observed with the lattice spacings of 0.230 nm, corresponding to the {111}p lane of face-centered cubic (fcc) PtCu. It is noted that the lattice fringes are discontinuous,i mplying that the formation of PtCu nanowires may originate from the oriented attachment of primary nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers also designed the core–shell Pt nanowires to enhance the electrocatalytic performance, since it not only increases the utilization of Pt atoms, but also amplifies the specific activity via strain effect and electronic effect. A typical example is demonstrated by Pd/Pt core–shell nanowires, which show outstanding area and mass activities of 0.77 mA cm −2 and 1.83 A mg Pt −1 , respectively . The ORR activity was further improved after introducing Au into Pd core, since Au can reduce Pt dissolution and migration.…”
Section: Pg‐based Nanowires For Enhanced Electrochemical Applicationsmentioning
confidence: 99%
“…[74] More recently, Crooks' group reported that Au@Pt NPs are better electrocatalysts than monometallic PtNPs and AuNPs for the cathodic reaction governing proton-exchangemembrane fuel cells (PEMFCs), namely the oxygen-reduction reaction (ORR). [77] Multi-metallic nanocatalysts have been designed by control of their components on the basis of the activity/selectivity in various reactions. [76] Very recently this research group has designed the synthesis, using GR, of polyamidoamine (PAMAM) dendrimer-encapsulated trimetallic Pd@Pt-Au nanowires, as efficient electrocatalysts for the ORR.…”
Section: Applications Of Bi-and Multimetallic Nanomaterials Synthesizmentioning
confidence: 99%